Gairaigo Dalam Majalah Nippon Ditinjau Dari Segi Pembentukan Kata - Yulianto, Uky (Jurnal Ilmiah Mahasiswa FIB, 2013)
One of the characteristics of language is dynamic. Therefore, the language is always changing to keep track of people as speakers. The development of culture, science, and technology are also the factors were affecting changes in language. That’s why, there are  new words called loan words. There are two problems to be solved in this study, namely : (1) What type of word formation is in the magazine  Nippon No. 3 (2) How does the frequency of the appearance of words formation’s types in the magazine Nippon No.3. This study uses qualitative descriptive type. The data source was used in this study is the loan words wich found in the magazine Nippon No.3 year 2009. The analysis is to do with the classification of the vocabulary, tabulation, and analysis of data. As the result there are 150 words of data included in gairaigo. The process of the formation that appears in the source data, is affixation (8 words), abbreviation (97 words), wasei gairaigo (7 words), and mixing (38 words).  Of all the types of word formation, the type of abbreviation is the most common form, which contained 97 words. From the abbreviations type, the type of word formation without the cutting is the most common, which is 81 words.   Key words : Loan words, Magazines, Morphology.